Histological Characteristic that Accompanying with Ovaryfolliculogenisis of Rabbits for Effectiveness Seeds of (Trigonellatibetana) (Medico Legal Update, 2020)
Objectives: Alternative plants Medicine has been considered one of the world’s most important solutions tofemale reproductive diseases. The goal of the current study however, was to evaluate the mains histologicalchanges that follow the use of seeds of (Trigonellatibetana) on ovary folliculogenisis.Method: Twelve’s female healthy rabbits, in animal house all experimental animals have been adapted.For this study, animals were taken distributed into two groups, control administrated by distal water (5 ml/kg b.w) and treatment group was administered by Trigonellatibetana extract at a dose of 2g/kgb.w/orallyadministration during 2 week for 3 time daily.Results: The present study finding the numerouschanges happened in the ovary, the mains variance has beennoticed increase the numbers of primordial and atretic follicles in treatment group and increase in size offollicles. Moreover, the theca interna was thickness and has a thicker layers of collagen than control group.Conclusions: Such results indicate that (Trigonellatibetana) was considered to be suitable for early fertilityperiod arrival.